2016
DOI: 10.1016/j.immuni.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

CD5 Binds to Interleukin-6 and Induces a Feed-Forward Loop with the Transcription Factor STAT3 in B Cells to Promote Cancer

Abstract: SUMMARY The participation of a specific subset of B cells and how they are regulated in cancer is unclear. Here, we demonstrate that the proportion of CD5+ relative to interleukin-6 receptor α (IL-6Rα) expressing B cells was greatly increased in tumors. CD5+ B cells responded to IL-6 in the absence of IL-6Rα. IL-6 directly bound to CD5, leading to activation of the transcription factor STAT3 via gp130 and its downstream kinase JAK2. STAT3 upregulated CD5 expression, thereby forming a feed-forward loop in the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
101
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(108 citation statements)
references
References 56 publications
2
101
1
1
Order By: Relevance
“…The importance of B cell subsets in cancer immunity was made apparent in a recent study demonstrating that IL-6 dependent activation of STAT3, which had long been associated with chronic inflammation in the tumor microenvironment [44,56,115], was confined to the subpopulation of CD5+, but not CD5− B cells [116]. CD5+ B cell numbers and STAT3 activation correlated with poor survival…”
Section: Perspectives and Final Thoughtsmentioning
confidence: 99%
“…The importance of B cell subsets in cancer immunity was made apparent in a recent study demonstrating that IL-6 dependent activation of STAT3, which had long been associated with chronic inflammation in the tumor microenvironment [44,56,115], was confined to the subpopulation of CD5+, but not CD5− B cells [116]. CD5+ B cell numbers and STAT3 activation correlated with poor survival…”
Section: Perspectives and Final Thoughtsmentioning
confidence: 99%
“…Although CD5 is considered primarily to be a regulator of TCR and B cell receptor (BCR) signaling (and therefore complexed to TCR or BCR), a recent study demonstrated that IL-6 can signal via CD5 (Zhang et al, 2016). The identification of functional signaling through CD5 that appears independent of its antigen receptor regulatory functions suggests that it could be expressed and function independently of the antigen receptor complex.…”
mentioning
confidence: 99%
“…Our data show that in CLL cells, CD5 contributes to STAT3 phosphorylation, as transfection of CLL cells with CD5-siRNA significantly downregulated CD5 mRNA and protein levels and markedly reduced the levels of serine pSTAT3. In addition, CD5-neutralizing antibodies, known to inhibit the activation of CD5, significantly reduced CD5 and serine pSTAT3 protein levels in CLL cells, likely because CD5 and STAT3 form a feed-forward loop (33). …”
Section: Discussionmentioning
confidence: 99%